2013
DOI: 10.1002/ana.23893
|View full text |Cite
|
Sign up to set email alerts
|

JC virus antibody status underestimates infection rates

Abstract: Background JC virus (JCV) seropositivity is a risk factor for progressive multifocal leukoencephalopathy (PML) in patients on natalizumab. Accordingly, the JCV serological antibody test is of paramount importance in determining disease risk. Methods We tested the accuracy of the JCV serum antibody test by comparing the results of JCV serology to JC viruria and viremia in 67 patients enrolled in a single-center, retrospective cohort study. Bodily fluids (urine and blood) were assessed for JCV DNA by real time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 33 publications
4
61
0
Order By: Relevance
“…Other countries should follow soon with the publication of their data to help assess the worldwide prevalence of JCV in MS patients requiring treatment with natalizumab. In understanding the serum anti-JCV status of MS patients, clinicians also need to know that this result underestimates infection levels since the false negative rates have been calculated as high as 37% 9 . This additional fact, recently reported in the literature, states that a negative JCV antibody result should not be conflated with absence of JCV infection 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other countries should follow soon with the publication of their data to help assess the worldwide prevalence of JCV in MS patients requiring treatment with natalizumab. In understanding the serum anti-JCV status of MS patients, clinicians also need to know that this result underestimates infection levels since the false negative rates have been calculated as high as 37% 9 . This additional fact, recently reported in the literature, states that a negative JCV antibody result should not be conflated with absence of JCV infection 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In understanding the serum anti-JCV status of MS patients, clinicians also need to know that this result underestimates infection levels since the false negative rates have been calculated as high as 37% 9 . This additional fact, recently reported in the literature, states that a negative JCV antibody result should not be conflated with absence of JCV infection 9 . In fact, there are reports of PML caused by the JCV in natalizumab-treated patients with negative JCV test results 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Natalizumab is a monoclonal antibody (MAb) directed against the very late antigen 4 (VLA-4) that directs migration and infiltration of immune cells into inflamed tissues (27). The risk of developing PML when taking natalizumab varies depending on a number of factors, including prior exposure to immunosuppressive therapies, JCPyV seropositivity, and duration of treatment (28). The risk can reach 1:100, if the duration of the treatment exceeds 25 months in individuals with a record of prior immunosuppressive therapies and JCPyV-seropositive status (available for prescribing physicians at https://medinfo.biogenidec.com).…”
mentioning
confidence: 99%
“…In another study, HLA-DRB1*15 was found to be associated with a negative JCPyV serostatus in MS patients, as measured by a commercial assay (31). The authors propose that serological assays might underestimate JCPyV infection status, with potential consequences for MS patients falsely identified as not exposed to JCPyV (32). We conclude that an improved serological assay with preadsorption for antibody activities around the cutoff is a critical first analysis to classify patients concerning JCPyV exposure.…”
Section: Discussionmentioning
confidence: 83%